Innovation Management Model of World Heritage City Museum on Historical Park for Creative Tourism in the Lower Part of Northern Thailand - Benjawan, Kununya; Thoongsuwan, Amorn; Pavapanunkul, Shayut (Asian Interdisciplinary and Sustainability Review, 2019)
This research synthesized the relevancy between the service quality management in museum influences and the growth trend towards creative tourism subsidiaries to earning a competitive advantage and promoting cultural heritage. The benefits of it in the end will lead to higher income and differentiating from its competitors, including better of creative tourism sustainability. SERVQUAL model led to the creation of the HISTOQUAL model analysis revealed that higher practicing of subsidiary growth model for a long time related to achieved through both (a) a higher practicing of service quality management in museum influences founding and (b) to examine visitors perceptions and expectations. These results suggest that purpose of this research study to synthesize the HISTOQUAL model is modified to suit to measure the service quality in museum influences. This research results point to the importance of the HISTOQUAL model that influence able discussion on culminates in a new research model with practicing innovation management model of this research propositions.